A simulation study on the effect of optimized high permittivity materials on fetal imaging at 3T - Gemert, Jeroen; Brink, Wyger; Remis, Rob; Webb, Andrew (Magnetic resonance in medicine, 2019)
Purpose One of the main concerns in fetal MRI is the radiofrequency power that is absorbed both by the mother and the fetus. Passive shimming using high permittivity materials in the form of “dielectric pads” has previously been shown to increase the B1+ efficiency and homogeneity in different applications, while reducing the specific absorption rate (SAR). In this work, we study the effect of optimized dielectric pads for 3 pregnant models. Methods Pregnant models in the 3rd, 7th, and 9th months of gestation were used for simulations in a birdcage coil at 3T. Dielectric pads were optimized regions of interest (ROI) using previously developed methods for B1+ efficiency and homogeneity and were designed for 2 ROIs: the entire fetus and the brain of the fetus. The SAR was evaluated in terms of the whole‐body SAR, average SAR in the fetus and amniotic fluid, and maximum 10 g‐averaged SAR in the mother, fetus, and amniotic fluid. Results The optimized dielectric pads increased the transmit efficiency up to 55% and increased the B1+ homogeneity in almost every tested configuration. The B1+‐normalized whole‐body SAR was reduced by more than 31% for all body models. The B1+‐normalized local SAR was reduced in most scenarios by up to 62%. Conclusion Simulations have shown that optimized high permittivity pads can reduce SAR in pregnant subjects at the 3rd, 7th, and 9th month of gestation, while improving the transmit field homogeneity in the fetus. However, significantly more work is required to demonstrate that fetal imaging is safe under standard operating conditions.